Effects of supplementation of sodium acetate on rumen fermentation and microbiota in postpartum dairy cows - Cheng, Zhiqiang; Meng, Zitong; Tan, Dejin; Datsomor, Osmond; Zhan, Kang; Lin, Miao; Zhao, Guoqi (Frontiers in Microbiology, 2022)
The primary product of rumen fermentation is acetic acid, and its sodium salt is an excellent energy source for post-partum cows to manage negative energy balance (NEB). However, it is unknown how adding sodium acetate (NAc) may affect the rumen bacterial population of post-partum cows. Using the identical nutritional total mixed ration (TMR), this research sought to characterize the impact of NAc supplementation on rumen fermentation and the composition of bacterial communities in post-partum cows. After calving, 24 cows were randomly assigned to two groups of 12 cows each: a control group (CON) and a NAc group (ACE). All cows were fed the same basal TMR with 468 g/d NaCl added to the TMR for the CON group and 656 g/d NAc added to the TMR for the ACE group for 21 d after calving. Ruminal fluid was collected before morning feeding on the last day of the feeding period and analyzed for rumen bacterial community composition by 16S rRNA gene sequencing. Under the identical TMR diet conditions, NAc supplementation did not change rumen pH but increased ammonia nitrogen (NH3-N) levels and microbial crude protein (MCP) concentrations. The administration of NAc to the feed upregulated rumen concentrations of total volatile fatty acids (TVFA), acetic, propionic, isovaleric and isobutyric acids without affecting the molar ratio of VFAs. In the two experimental groups, the Bacteroidota, Firmicutes, Patescibacteria and Proteobacteria were the dominant rumen phylum, and Prevotella was the dominant rumen genus. The administration of NAc had no significant influence on the α-diversity of the rumen bacterial community but upregulated the relative abundance of Prevotella and downregulated the relative abundance of RF39 and Clostridia_UCG_014. In conclusion, the NAc supplementation in the post-peripartum period altered rumen flora structure and thus improved rumen fermentation in dairy cows. Our findings provide a reference for the addition of sodium acetate to alleviate NEB in cows during the late perinatal period.